Discovery of a bright extended X-ray jet in RGB J1512+020A. Issue 3 (24th February 2022) - Migliori, G; Siemiginowska, A; Cheung, C C; Celotti, A; Giroletti, M; Giovannini, G; Paggi, A; Liuzzo, E
ABSTRACT: We report the discovery of a bright, extended X-ray jet in the quasar RGB J1512+020A ( z = 0.22). Chandra  observations show the X-ray core and 13 arcsec  (∼45 kpc projected) extended emission coincident with the radio jet. The jet stands out as one of brightest X-ray jets ( LX ∼ 7 × 10 43 erg s −1 ) at low redshift (z < 0.5) discovered so far, with remarkably large X-ray to radio luminosity ratios ( LX / Lr up to ∼50). We identified four main components, two unresolved knots and two extended structures, one being the jet brightest feature (JBF). All jet features are also detected in ALMA archival observations. The radio, sub-mm to X-ray spectra of the two knots can be modelled with a single synchrotron component. For the two resolved structures, the ALMA data unveil a turnover of the low-energy continuum at ∼460 GHz. External Comptonization of cosmic microwave background photons can account for the observed X-ray emission if the jet speed remains highly relativistic, with bulk motion Γbulk > 15, up to tens of kiloparsec from the core. However, the comparison with the spectral energy distribution of similar X-ray detected jets shows that the alternative hypothesis of synchrotron emission from an additional population of ultra-high-energy electrons is also possible. We report a tentative (≳2σ) optical detection of the JBF in images of the Dark Energy Camera Legacy Survey. If confirmed, the optical emission should be either the low-energy tail of the radiative component responsible for the X-ray emission or a third, separate component.